2017
DOI: 10.1152/ajplung.00531.2016
|View full text |Cite
|
Sign up to set email alerts
|

Central role of T helper 17 cells in chronic hypoxia-induced pulmonary hypertension

Abstract: Inflammation is a prominent pathological feature in pulmonary arterial hypertension, as demonstrated by pulmonary vascular infiltration of inflammatory cells, including T and B lymphocytes. However, the contribution of the adaptive immune system is not well characterized in pulmonary hypertension caused by chronic hypoxia. CD4 T cells are required for initiating and maintaining inflammation, suggesting that these cells could play an important role in the pathogenesis of hypoxic pulmonary hypertension. Our obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 60 publications
9
63
1
Order By: Relevance
“…Under physiological conditions, Th17 and Treg are in a dynamic equilibrium. In PAH, the balance of Th17 and Treg is broken, and Th17 cells, which have proinflammatory effects, are increased, and the activation of Treg cells, which exert anti-inflammatory protective effects, is reduced [39]. Osman and colleagues found that Tregs suppressed inflammation, immune dysregulation and vascular remodeling in females and that they thereby exert a protective effect in PAH models [33].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, Th17 and Treg are in a dynamic equilibrium. In PAH, the balance of Th17 and Treg is broken, and Th17 cells, which have proinflammatory effects, are increased, and the activation of Treg cells, which exert anti-inflammatory protective effects, is reduced [39]. Osman and colleagues found that Tregs suppressed inflammation, immune dysregulation and vascular remodeling in females and that they thereby exert a protective effect in PAH models [33].…”
Section: Discussionmentioning
confidence: 99%
“…Maston et al 34 found that RAG1 −/− mice, which lack mature T and B cells, exhibited and attenuated HPH phenotype, while the adoptive transfer of CD4 + T cells or Th17 cells could restore this process. However, the role of IL-17 in PH pathology is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular suspension was prepared by enzymatically digesting the lungs as previously reported. 16 Lung IL-6, sIL-6R, and sgp130 levels were normalized to total protein determined by the Bradford method (Biorad).…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary arterial remodeling was assessed using a modification of previously published methods. 16 After collection of hemodynamic data, the lungs were perfused via the RV with ∼5 mL of modified physiological saline solution (HEPES-PSS, 134 mM NaCl, 6 mM KCl, 1 mM MgCl 2 , 10 mM HEPES, 2 mM CaCl 2 , 0.026 mM EDTA, and 10 mM glucose) containing heparin, 4% albumin (Sigma), and 10 −4 M papaverine (Sigma), at 20 mmHg to maximally dilate and flush the circulation of blood. The heart, lungs, and trachea were removed in block, and the lungs inflated through the trachea with the same solution.…”
Section: Methodsmentioning
confidence: 99%